2017
DOI: 10.1016/j.jpurol.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Pneumovesical ureteric reimplantation using T-fastener: A modification for bladder wall anchorage

Abstract: In our experience, this technique is simple to learn and transferrable. It decreases intraoperative complications and helps to climb the learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…8,9 Lau et al reported bladder suspension with a T-shaped commercially available single-use equipment without any complication related to it, but the cost and availability of the device are the factors restricting its use. 5 Home made T-bar system is inexpensive, simple, and reliable. The ureteral catheter at the end of the T-bar prevents bladder tearing by distributing the traction force on the wider surface of the bar, provides more stable fixation for bladder wall and for the working ports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Lau et al reported bladder suspension with a T-shaped commercially available single-use equipment without any complication related to it, but the cost and availability of the device are the factors restricting its use. 5 Home made T-bar system is inexpensive, simple, and reliable. The ureteral catheter at the end of the T-bar prevents bladder tearing by distributing the traction force on the wider surface of the bar, provides more stable fixation for bladder wall and for the working ports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] One of the crucial steps of pneumovesicoscopy is fixing the bladder wall to the abdominal wall as failure of this step may result in complications, termination of pneumovesicoscopy, and conversion to open surgery. 5 Some special devices such as locking trocars, ports with umbrella, and single-use lifting equipments have been commercially introduced for bladder fixation. 2,5 Although they are very useful and practical, they have not gained widespread acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation